Catalytic oxidation upcycling of polyethylene terephthalate to commodity carboxylic acids - Qinghai Chen; Hao Yan; Kai Zhao; Shuai Wang; Dongrui Zhang; Yaqian Li; Rong Fan; Jie Li; Xiaobo Chen; Xin Zhou; Yibin Liu; Xiang Feng; et al. (Nature Communications)
Abstract Catalytic upcycling of polyethylene terephthalate (PET) into high-value oxygenated products is a fascinating process, yet it remains challenging. Here, we present a one-step tandem strategy to realize the thermal catalytic oxidation upcycling of PET to terephthalic acid (TPA) and high-value glycolic acid (GA) instead of ethylene glycol (EG). By using the Au/NiO with rich oxygen vacancies as catalyst, we successfully accelerate the hydrolysis of PET, accompanied by obtaining 99% TPA yield and 87.6% GA yield. The results reveal that the oxygen vacancies in NiO (NiO-Ov) support tend to adsorb hydrolysis product TPA, preferentially ensuring the strong adsorption of EG at the Au-NiO interface. Moreover, during the EG oxidation process, the Au-NiO interface, composed of two types of structures, quasi “AuNi alloy” and NiO-Ov, simultaneously promote the C-H bond activation, where Ni in “AuNi alloy” exhibits an oxytropism effect to anchor the C = O bond of the intermediate, while the residual O in NiO-Ov pillages the H in the C-H bond. Such Au/NiO catalyst is further extended to promote the thermal catalytic oxidation upcycling of other polyethylene glycol esters to GA with excellent catalytic performance.